STRUCTURE DESIGN OF PARKING BUILDING SUNTER PARK VIEW APARTMENT WITH THE EQUIVALENT STATIC ANALYSIS METHOD - Wuritno, Bambang (Semarang State University, 2013)
Parking building (Tower C), Project Sunter Park View Apartment is a public facility that serves as a parking garage. This building consists of 4 floors including the roof plate with a typical floor plan for each level. Floor to floor elevation is 3 meters height, so the total height of the building reach 9 meters height (less than 40 meters height). Review Design Parking building structure (Tower C) Project Title: